2023
DOI: 10.26434/chemrxiv-2022-pbt49-v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large Decrease in Melting Point of Benzoquinones via High-n Eutectic Mixing Predicted by a Regular Solution Model

Abstract: Decreasing the melting point (Tm) of a mixture is of interest in cryopreservatives, molten salts, and battery electrolytes. One general strategy to decrease Tm, exemplified by deep eutectic solvents, is to mix components with favorable (negative) enthalpic interactions. We demonstrate a complementary strategy to decrease Tm by mixing many components with neutral or slightly positive enthalpic interactions, using the number of components (n) to increase the entropy of mixing and decrease Tm. In theory, under ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…30−32 In these systems the redox-active species is not a eutectic component, resulting in similar limitations to other solvent-led approaches, including low solubility of redox-active species and high viscosity. 33 Our approach, which theoretically could achieve the highest energy density of the above approaches, uses eutectic mixing to lower the melting points of mixtures composed entirely of redox-active components. Our prior work 34 shows that if these compounds have similar molecular structures, the change in enthalpy upon mixing will likely be small, and a decrease in the melting point will be driven by the entropy of mixing, which increases with the number of distinct components in the mixture.…”
Section: ■ Eutectic Electrolytes In Flow Batteriesmentioning
confidence: 99%
“…30−32 In these systems the redox-active species is not a eutectic component, resulting in similar limitations to other solvent-led approaches, including low solubility of redox-active species and high viscosity. 33 Our approach, which theoretically could achieve the highest energy density of the above approaches, uses eutectic mixing to lower the melting points of mixtures composed entirely of redox-active components. Our prior work 34 shows that if these compounds have similar molecular structures, the change in enthalpy upon mixing will likely be small, and a decrease in the melting point will be driven by the entropy of mixing, which increases with the number of distinct components in the mixture.…”
Section: ■ Eutectic Electrolytes In Flow Batteriesmentioning
confidence: 99%
“…We limited our search to compounds with a molecular weight of less than 216 g/mol for the quinone-based molecules and 204 g/mol for the hydroquinone-based molecules: our database was initially created with the goal of identifying small quinones/hydroquinones as candidate molecules in a solvent-free eutectic mixture flow battery electrolyte. 21 We then filtered the data by compounds which had melting points available from the literature and downloaded them using Reaxys's download feature. The molecular weights from Reaxys were also included as features in the ML models.…”
Section: ■ Experimental Detailsmentioning
confidence: 99%
“…15−18 In order to identify promising materials for eutectic electrolytes, determining the melting temperatures of the quinone and hydroquinone molecules is essential. 19 With an effective approximation of the regular solution model, 20,21 the melting points of the single-component quinones and hydroquinones can be used to predict the melting point of a eutectic mixture. However, melting data is not readily available for all of the quinones and hydroquinones of interest, so having a model that predicts the melting points of quinone and hydroquinone molecules is highly desirable.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Zhang et al 22 used this method to design Li-ion electrolytes that remained in the liquid phase as low as −130 °C, while Cho et al 23 utilized the same calculation to develop carbonate−nitrile Li-ion electrolytes capable of maintaining the liquid form down to −110 °C. The method has also been used to predict eutectic points in benzoquinones 24 and many other solvents. 25 Similarly, work by Schoetz et al 7 on IL electrolytes for Al batteries has shown that increasing the entropy of the liquid phase has general success in depressing the freezing point.…”
Section: ■ Introductionmentioning
confidence: 99%